Nasal Bubble Continuous Positive Airway Pressure: An Experience in a Neonatal Unit in a Tertiary Teaching Hospital in Pokhara - Basnet, Sahisnuta; Adhikari, Suraj; Mishra, Aparna (Journal of Nepal Paediatric Society, 2021)
Introduction: Nasal bubble continuous positive airway pressure (NBCPAP) is a modality used for respiratory distress in newborns and provides respiratory support by preventing atelectasis and reducing the work of breathing. The objective of this study was to determine the efficacy, outcomes and complications of NBCPAP in term and preterm newborns requiring NBCPAP. Methods:A prospective observational study was conducted on 75 neonates with mild to moderate respiratory distress requiring respiratory support from August 2020 to December 2020. Assessment of baseline characteristics, indications, complications and outcomes of NBCPAP was carried out on the studied newborns. Outcomes were considered as either success (improvement) or failure (need for mechanical ventilation). Results: The median gestational age was 38 weeks (IQR:35-39 weeks). The median birth weight was 2600 gm (IQR: 2000- 3000 gm). The commonest indication for the requirement of NBCPAP was neonatal sepsis (34%). A total of 65 (86.7%) neonates could be successfully weaned off NBCPAP. Complications were noted in 23 neonates. Modified Downes score on admission (adjusted OR 5.34, 95% CI 1.75- 16.35) and gestational age (adjusted OR 0.68, 95% CI 0.51- 0.92) were independent predictors of failure of NBCPAP. Conclusions: NBCPAP can be successfully utilised in preterm and term babies with mild to moderate respiratory distress. The major predictors of failure of NBCPAP are decreasing gestational age and increasing Downes score.